Dekonstruksi dalam Cerpen Malin Kundang, Ibunya Durhaka Karya A.A. Navis - Zulfadhli Zulfadhli (Fakultas Bahasa dan Seni UNP, 2009)
This paper discusses the short story of Malin Kundang, rebellious mother, written by AA Navis by using Derrida’s deconstruction theory. Deconstruction is method of reading the text very carefully so that the conceptual distinction inventions by the authors of the foundations texts seem inconsistent and paradoxes in the use of the concept in the text as a whole. The presence of deconstruction has allowed a text to have multi meanings. Literary text is seen as very complex. In this short story, Navis does not imitate what it is from the legend, nor about the legend recounted his version, but argues on different sides of legend of Malin Kundang and delivers it in way that is very unique and interesting. In this short story, it was obvious that the deflation against the grand narrative is as one object of study in deconstruction Kata Kunci: dekonstruksi, cerpen, teks, ciptaan